Theoretical foundations for the study of social innovation in the public sector - Vogl, TM (Springer, 2020)
Over the past two decades, there have been significant debates around the theoretical foundations for the study of social and material implications of technological change in organizational settings. Various scholars have looked at these foundations with a focus on either the social and the material as discrete entities, the social and the material as interactive, the sociomaterial as a concept representing the constitutive entanglement of the two, or the sociomaterial as imbricated but analytically distinct. These debates sometimes lead to statements about which foundations are the most appropriate upon which to build studies; however, it may be more productive to delineate what each theoretical foundation affords for the study of social innovation. This paper sets out the affordances of each perspective for the design and execution of research into technologically supported social innovation in the public sector. It provides relevant examples from child protection services to illustrate where and how these different theoretical foundations help researchers to understand phenomena associated with social innovation. In so doing, this paper seeks to clarify the diverse approaches to the study of technologically supported social innovation, their assumptions, and where they may be adopted most effectively.